Place of agritourism in a balanced development of rural areas - Tschirschnitz, Hanna (Ecological Questions, 2013)
Short time prognosis for period between 2000 and 2020 assumes that deep transformation has to be performed at rural areas of Poland. The transformation process will cover of fields of rural development from agricultural sector, demography, sources of income, cultural life, etc. The significance of agriculture has been constantly as a trustee of big share of natural resources of Poland. Contrary to this in the structure of employment and in income of rural population agriculture will play a smaller role. It is evident that the main source of income will become service of agricultural sector. Multifunctional management of rural areas combined with rules of sustainable development can be very effective tool for protection of the natural environment which in large areas of Poland has unique values estimated as the highest degree of biodiversity in whole Europe is a tool for improvement of economical position of rural population. Sustainable development is aimed at protection of and maintenance of natural values what in indirect way can lead to improve of quality of life at rural areas. The important part of such attitude is agrotourism which is directly connected to utilization of environmental values of rural regions and it is a form of spending leisure time at the farm for wide public. Attractions connected with staying at rural environment are significant elements of management of rural landscape. Besides economical benefits effect of synergy should be mentioned which is seen as better care of natural environment and aesthetic values of surroundings.